La fiducie foncière - Moreau, Rémi (Assurances, 1992)
A land trust is a private, non-governmental and non-profit organization directly involved in the protection of lands solely for their natural and ecological values. This article summarizes the steps involved in creating a land trust, from establishing the incorporation, setting up a board of directors to organizing support and interest. The view expressed by the author is based on his recent experience in implementing and operating a land trust in Sainte-Adèle, Québec.